1963
DOI: 10.1071/ar9630154
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the Barley Yellow Dwarf Virus as a primary or associated cause of premature ripening or "Deadheads" in wheat

Abstract: In two controlled experiments conducted in 1960 and 1961 respectively, the ability of recognized root pathogens to induce premature ripening ("deadheads") of wheat was compared with that of the barley yellow dwarf virus, a hitherto uninvestigated factor in this regard. In both experiments the heads of virus-infected plants ripened earlier than those of plants inoculated with fungal pathogens, and grain in heads which were not completely sterile was extremely shrivelled. However, it was impossible to decide by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…R. padi was the most abundant and often the only cereal aphid in all districts and is undoubtedly the main vector of BYDV in Australia. This confirms the results of Butler, Grylls, and Goodchild (1960) in New South Wales; Geard (1960) in Tasmania; Harvey (1962) in Western Australia; and Price and Stubbs (1963) in Victoria-who have all previously found R. padi an efficient vector of BYDV.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…R. padi was the most abundant and often the only cereal aphid in all districts and is undoubtedly the main vector of BYDV in Australia. This confirms the results of Butler, Grylls, and Goodchild (1960) in New South Wales; Geard (1960) in Tasmania; Harvey (1962) in Western Australia; and Price and Stubbs (1963) in Victoria-who have all previously found R. padi an efficient vector of BYDV.…”
Section: Resultssupporting
confidence: 89%
“…The mast pramising methads of cantral of BYDV infectian in springsown cereals are: 1. early sowing; 2. sawing varieties more talerant to' BYDV infectian (Price and Stubbs 1963); 3. top-dressing crops with pelle ted systemic insecticides ("Disystan" or "Thimet") after the first aphid flights have colonised the crap; 4. encouraging early activity af caccinellids such as V. frenata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides direct damage the R. padi is the most important vector of barley yellow dwarf virus (BYDV) (Price & Stubbs, 1963;Ullman et al, 1988;McGrath & Bale, 1990). BYDV transmitted by R.…”
Section: Introductionmentioning
confidence: 99%
“…More recently. PRICE and STUBBS (1963) were unable to induce whiteheads experimentally with O. graminis and other root pathogens but did so with barley yellow dwarf virus. They concluded that there was insufficient evidence to positively associate root pathogens with premature ripening because the same fungi could be isolated from plants with normal heads.…”
Section: Introductionmentioning
confidence: 99%